5-HT1B receptor in the suprachiasmatic nucleus of the common marmoset (Callithrix jacchus) - Cavalcante, Jeferson S.; de Pontes, Andre L. B.; Engelberth, Rovena C. G. J.; Cavalcante, Judney C.; Nascimento, Expedito S.; Borda, Janaina S.; Pinato, Luciana [UNESP]; Costa, Miriam S. M. O.; de Toledo, Claudio A. B. (Elsevier B.V., 2011)
Serotonin (5-HT) is involved in the fine adjustments at several brain centers including the core of the mammal circadian timing system (CTS) and the hypothalamic suprachiasmatic nucleus (SCN). The SCN receives massive serotonergic projections from the midbrain raphe nuclei, whose inputs are described in rats as ramifying at its ventral portion overlapping the retinohypothalamic and geniculohypothalamic fibers. In the SCN, the 5-HT actions are reported as being primarily mediated by the 5-HT1 type receptor with noted emphasis for 5-HT1B subtype, supposedly modulating the retinal input in a presynaptic way. In this study in a New World primate species, the common marmoset (Callithrix jacchus), we showed the 5-HT1B receptor distribution at the dorsal SCN concurrent with a distinctive location of 5-HT-immunoreactive fibers. This finding addresses to a new discussion on the regulation and synchronization of the circadian rhythms in recent primates. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Suprachiasmatic nucleus; Serotonin receptor; Callithrix jacchus; Primate; Circadian timing system; Serotonin